UPAYA PENINGKATAN PENGETAHUAN TENTANG KESEHATAN JIWA PADA REMAJA MELALUI PENYULUHAN DI SMA KOTA KUPANG - Flavianus Riantiarno; Israil Yuan Umbu Wanda; Serli Kause; Maria Intania Vanesa Asury; Obed Buni Pona; Ermawati Yaku Danga; Savitri Rambu Juni Rana; Merlin Nenoso (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Mental health problems are a matter of concern. Mental health problems in adolescents is one of them. Teenagers must be mentally healthy. In recent years, adolescent mental health has become a growing concern. There is an increasing prevalence of mental health problems in adolescents. One of the prevention efforts is prevention by educating adolescents about mental health. This activity aims to increase the knowledge of high school youth (SMA) about mental health. This activity was carried out by lecturers and students of STIKes Maranatha Kupang. Schools that become partners are schools that are willing to provide health education to their students. This activity was carried out in four senior high schools (SMA) in Kupang City. The results show that there is a good increase in students' knowledge about mental health. It is hoped that with this activity, youth will know about mental health and be able to prevent students from experiencing mental health problems